Action observation and imitation in Parkinson's disease: The influence of biological and non-biological stimuli. (8th January 2021) - Bek, Judith; Gowen, Emma; Vogt, Stefan; Crawford, Trevor J.; Poliakoff, Ellen
Abstract: Action observation and imitation have been found to influence movement in people with Parkinson's disease (PD), but simple visual stimuli can also guide their movement. To investigate whether action observation may provide a more effective stimulus than other visual cues, the present study examined the effects of observing human pointing movements and simple visual stimuli on hand kinematics and eye movements in people with mild to moderate PD and age-matched controls. In Experiment 1, participants observed videos of movement sequences between horizontal positions, depicted by a simple cue with or without a moving human hand, then imitated the sequence either without further visual input (consecutive task) or while watching the video again (concurrent task). Modulation of movement duration, in accordance with changes in the observed stimulus, increased when the simple cue was accompanied by the hand and in the concurrent task, whereas modulation of horizontal amplitude was greater with the simple cue alone and in the consecutive task. Experiment 2 compared imitation of kinematically-matched dynamic biological (human hand) and non-biological (shape) stimuli, which moved with a high or low vertical trajectory. Both groups exhibited greater modulation for the hand than the shape, and differences in eye movements suggested closer tracking of the hand. Despite producing slower and smaller movements overall, the PD group showed a similar pattern of imitation to controls across tasks and conditions. The findings demonstrate that observing human action influences aspects of movement such as duration or trajectory more strongly than non-biological stimuli, particularly during concurrent imitation. Highlights: People with PD showed similar patterns to controls when imitating hand movements. Imitation of duration and trajectory was greater for biological stimuli. Concurrent observation increased imitation of movement duration. Eye movements indicated closer tracking of biological than non-biological stimuli. Action observation and simple visual cues can influence different aspects of movement.